Public office, private interest bureacracy and corruption in India - Das, S. K., 1945- (New Delhi ; Oxford : Oxford University Press, 2001)
Written by a senior civil servant, this book looks at public bureaucracy in India which has ended up serving the narrow interests of patrimonial politics, especially after independence.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political corruption -- India; Bureaucracy -- India